2021
DOI: 10.1021/acs.jpcc.0c05382
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Fission Dynamics in the 5,12-Bis(phenylethynyl)tetracene Thin Film

Abstract: The singlet fission (SF) process is a promising route to overcome the Shockley and Quiesser efficiency limit of organic solar cells and hence has attracted significant research interest in the recent past. Efficient SF in low-cost organic materials with broad visible absorption is desirable to potentially boost organic solar cell efficiency. Herein, we report the ultrafast and efficient SF property of a new molecular material, namely, the 5,12-bis(phenylethynyl)tetracene (BPET) thin film. Steady-state and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…A thin film of DBPn was prepared by the physical vapor deposition method under low pressure conditions (∼10 –6 mbar). , The deposition of the sample was done by employing SMART COAT 3 from Hind High Vac. (India).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A thin film of DBPn was prepared by the physical vapor deposition method under low pressure conditions (∼10 –6 mbar). , The deposition of the sample was done by employing SMART COAT 3 from Hind High Vac. (India).…”
Section: Methodsmentioning
confidence: 99%
“…Singlet fission (SF) is a sought-after property of organic semiconductors having potential for overcoming the Shockley–Quisser efficiency limit of organic photovoltaics. It is a process where a photogenerated singlet exciton is converted to two triplet excitons resulting in more than 100% excitonic yield, paving the way for fabrication of efficient organic solar cells. However, this property is restricted to only a few classes of organic molecules due to stringent energetic and molecular coupling criteria. Efficient SF is exhibited by molecular systems having the lowest excited singlet (S 1 ) energy levels twice that of the lowest triplet (T 1 ) energy level, that is, it must fulfill E­(S 1 ) ≥ 2E­(T 1 ) energetic criteria. In addition, SF involves an electron spin-exchange process, which requires an orbital overlap and introduces the strict requirement of strong intermolecular coupling. , Polyacenes, carotenoids, isobenzofurans, perylenebisimides, terylenes, and diketopyrrolopyrrole derivatives are mostly reported to exhibit this exceptional property. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that, for the high excitation energy of 4 μJ/pulse, the triplet ESA band achieves the maximum signal by 0.3 ps, while for 0.8 μJ/pulse, the triplet ESA band is found to grow even up to 20 ps delay. Such fast triplet exciton formation is reported for systems having the scope of singlet fission process. However, considering the endoergic nature (2 E T1 – 2 E S1 ∼ 0.6 eV) of this present anthracene derivative, the possibility of involvement of singlet fission is very unlikely. S 2 - or hot S 1 -mediated singlet fission was also reported recently for some polyaromatic systems. , However, in the present case, reduction in the triplet formation rate was observed upon the reduction of the excitation intensity.…”
Section: Results and Discussionmentioning
confidence: 67%
“…There are reports where the singlet fission is found to occur within the 100 fs timescale. 55,59 Hence, following similar spin exchange mechanism, triplet formation is also not unjustified during the singlet−singlet exciton annihilation process. Here, one triplet excitonic level forms, which is lower in energy as compared to the S 1 energy level, and the other triplet state (T m ) formed in the same equation will have a higher energy level as compared to S 1 .…”
Section: Methodsmentioning
confidence: 93%